Inhibitor potency and assay conditions: a case study on SARS-CoV-2 main protease - Behnam, Mira A. M.; Klein, Christian D. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Li et al. (1) report known drugs as inhibitors of the main protease (Mpro) of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The compounds, including atazanavir, were initially identified by virtual screening, followed by fluorescence resonance energy transfer (FRET)-based biochemical inhibition assays. - - In this letter, we demonstrate that the inhibitory activity achieved in enzymatic assays by the compounds is sensitive to the conditions used. This observation supports the proposed conformational selection paradigm for SARS-CoV-2 Mpro (2). - - Using an Mpro with C-terminal His-tag and the FRET substrate Abz-VVTLQ/SGDap(Dnp)R-OH (3), atazanavir showed no or minimal inhibition under all studied conditions, including the buffer used by Li et al. (1) This point was previously raised by Ma and Wang (4), and, in comparison to their substrate Dabcyl-KTSAVLQ/SGFRKME(Edans) (5), our shorter substrate renders an influence of substrate length less likely and pinpoints the difference in … To whom correspondence may be addressed. Email: mira.behnamuni-heidelberg.de or c.kleinatuni-heidelberg.de.